LOWER AMU DARYA SANDY DESERTS EUCEROPHYTIC (PSAMMOTHAMNA) SHRUBS - Allambergenova, N.B.; Azhiev, A.B. (SCIENCE and SOCIETY, 2026)
The article provides information on the current state of vegetation in the lower reaches of the Amu Darya, its successional changes due to the reduction in the Amu Darya River's flow, and the euxerophytic vegetation, which is divided into several variants of tugai forests and formations. The main euxerophytic formation consists of 5 associations, the primary components of which are the juzgun - Calligonum caput-medusae and the cherkez - Xylosalsola richteri (Moq.) Akhani & Roalson.
Keywords: plant formations; associations; euxerophytic vegetation; lower reaches of the Amu Darya; flow reduction; delta tugai forests; etc.